Application of electronic control systems to train navigation - Dy, Jovanni (Animo Repository, 1997)
The meaning of train transportation has changed from being optional to necessity. These train systems are now automated and never-ending improvements are still going on. When these trains were operated, they will run smoothly one station after another. Various sensors, installed internally and externally serving as accident-mitigation system to the train, help the driver a lot in operating the machine. Furthermore, additional devices were installed that will help him and the passengers be more comfortable. The accuracy and speed of these devices plus the human skills will provide the whole transportation system with the best efficiency the whole world can ever imagine.